Imperial fictions - Kontje, Todd Curtis (University of Michigan Press, 2018)
Introduction – National origins and the imperial past – German literary history and the medieval renaissance – Silesian patriots and imperial subjects – Goethe and the end of the Holy Roman Empire – Romantic nationalism and imperial nostalgia – Worldly provincialism in imperial Germany – Collapsing empires and nascent nations – Revisiting the Heimat after the Third Reich – Popular fiction and the imperial past – Conclusion : national literature in an era of world literature Imperial Fictions explores ways in which writers from late antiquity to the present have imagined communities before and beyond the nation-state. It takes as its point of departure challenges to the discrete nation-state posed by globalization, migration, and European integration today, but then circles back to the beginnings of European history after the fall of the Roman Empire. Unlike nationalist literary historians of the nineteenth century, who sought the tribal roots of an allegedly homogeneous people, this study finds a distant mirror of analogous processes today in the fluid mixtures and movements of peoples. Imperial Fictions argues that it is time to stop thinking about today’s multicultural present as a deviation from a culturally monolithic past. We should rather consider the various permutations of “German” identities that have been negotiated within local and imperial contexts from the early Middle Ages to the present.
9780472130788
Keywords: German literature; Imperialism in literature; Nationalism in literature; National characteristics; German; in literature